2018
DOI: 10.2196/medinform.8479
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Health System Experience With Implementation of an Enterprise-Wide Telehealth Scheduled Video Visit Program: Mixed-Methods Study

Abstract: BackgroundReal-time video visits are increasingly used to provide care in a number of settings because they increase access and convenience of care, yet there are few reports of health system experiences.ObjectiveThe objective of this study is to report health system and patient experiences with implementation of a telehealth scheduled video visit program across a health system.MethodsThis is a mixed methods study including (1) a retrospective descriptive report of implementation of a telehealth scheduled visi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…Despite these limitations, the BGPaH evaluation provides useful information as a case study to inform current debates about the implementation of video-first services in primary care. In the United States, there have been brief reports about digital primary care based on video consultations from organizations such as Kaiser Permanante [ 14 - 16 ], Jefferson Health [ 17 , 18 ], and the Veteran’s Administration [ 19 ]. Several digital health platforms have been established in Sweden, and these have been reported in a descriptive evaluation, but this does not distinguish between video, audio, and text-based web-based consultations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the BGPaH evaluation provides useful information as a case study to inform current debates about the implementation of video-first services in primary care. In the United States, there have been brief reports about digital primary care based on video consultations from organizations such as Kaiser Permanante [ 14 - 16 ], Jefferson Health [ 17 , 18 ], and the Veteran’s Administration [ 19 ]. Several digital health platforms have been established in Sweden, and these have been reported in a descriptive evaluation, but this does not distinguish between video, audio, and text-based web-based consultations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Video visits provide a new way of conducting clinical meetings, potentially reducing costs and providing services for patients living in remote or rural areas [ 1 , 3 ]. There is no doubt that video visits can be beneficial for different stakeholders from different perspectives [ 1 , 3 ], but the implementation of telemedicine also causes changes in the organization of work; tasks and processes; and identities, roles, and authority, potentially affecting the power relationships among the participants; and participants’ expectations of the meeting (cf [ 4 - 7 ]). Recent research has shown that video visits in outpatient care settings appear to be safe, effective, and convenient; however, there are complex challenges related to their adoption by clinicians [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with video technology has been explored in surveys [ 9 ], but problems with technology are seldom explored in-depth [ 1 ]. Experiences regarding the implementation of video visits have not been examined very well [ 3 ], but recent research addresses the question of implementation and has generated five key recommendations concerning how technology should be introduced: iterative introduction with the involvement of staff, time for reflection with staff and patients, relations with the information and communication technology (ICT) department to establish roles and processes, understanding patients’ conditions, and flexibility of use to fit patients’ needs [ 8 ]. If video visits are going to be beneficial at the macro level, they need to attract users (ie, clinicians and patients) at the micro level by considering professional dimensions and meeting the users’ needs.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that patients living a long distance from the health care premises are offered telemedicine solutions, and physicians are recommended to begin with less complex cases [ 13 ]. The selection of patients for video visits may hence be determined by various criteria such as the complexity of the meeting, the patient’s preferences and distance from the clinic, the clinician’s experience with the technology, and so forth [ 2 ]. It is known that the physical clinical environment affects patient satisfaction, attitudes, and work performances [ 14 ], which implies that selecting patients for video visits needs careful consideration.…”
Section: Introductionmentioning
confidence: 99%